Originally Posted by

**vaironxxrd** Hello Everyone,

In preparation for an upcoming exam I've selected a derivative problem and attempted to solve it...

I have to use $\displaystyle f^'$$\displaystyle (x) = \frac{f(x+h)-f(x)}{h}$ to solve these problems.

My attempts:

a)$\displaystyle f(x) = 3x^3$ Using the book theorems I could quickly find the answer was $\displaystyle 9x^2$ Now I have to prove this...

$\displaystyle f^'$$\displaystyle (x) = \frac{3(x+h)^3-3x^3}{h}$ =

$\displaystyle \frac{3h^3+9h^2x+9hx^2+3x^3}{h}$ = (cancel h)

$\displaystyle 9x^2+3x^3$

This solution of course doesn't match $\displaystyle 9x^2$